Postural control strategy after incomplete spinal cord injury: effect of sensory inputs on trunk–leg movement coordination - Noamani, Alireza (J Neuroeng Rehabil, 2020)
BACKGROUND: Postural control is affected after incomplete spinal cord injury (iSCI) due to sensory and motor impairments. Any alteration in the availability of sensory information can challenge postural stability in this population and may lead to a variety of adaptive movement coordination patterns. Hence, identifying the underlying impairments and changes to movement coordination patterns is necessary for effective rehabilitation post-iSCI. This study aims to compare the postural control strategy between iSCI and able-bodied populations by quantifying the trunk–leg movement coordination under conditions that affects sensory information. METHODS: 13 individuals with iSCI and 14 aged-matched able-bodied individuals performed quiet standing on hard and foam surfaces with eyes open and closed. We used mean Magnitude-Squared Coherence between trunk–leg accelerations measured by accelerometers placed over the sacrum and tibia. RESULTS: We observed a similar ankle strategy at lower frequencies (f ≤ 1.0 Hz) between populations. However, we observed a decreased ability post-iSCI in adapting inter-segment coordination changing from ankle strategy to ankle–hip strategy at higher frequencies (f > 1.0 Hz). Moreover, utilizing the ankle–hip strategy at higher frequencies was challenged when somatosensory input was distorted, whereas depriving visual information did not affect balance strategy. CONCLUSION: Trunk–leg movement coordination assessment showed sensitivity, discriminatory ability, and excellent test–retest reliability to identify changes in balance control strategy post-iSCI and due to altered sensory inputs. Trunk–leg movement coordination assessment using wearable sensors can be used for objective outcome evaluation of rehabilitative interventions on postural control post-iSCI.